Exogenous Melatonin Attenuates Post-Harvest Decay by Increasing Antioxidant Activity in Wax Apple (Syzygium samarangense) - Chen, Yao; Zhang, Yanjie; Nawaz, Ghazala; Zhao, Chenxu; Li, Yuxia; Dong, Tingting; Zhu, Mingku; Du, Ximeng; Zhang, Lei; Li, Zongyun; Xu, Tao (Frontiers in Plant Science, 2020)
Wax apple is one of the most popular tropical fruit but undergoes serious post-harvest decay during storage, transportation and marketing. Melatonin (MT) plays important roles in plant growth, development and stress responses. However, its function in post-harvest preservation of fruit remains largely unknown. In the present study, the physiological function and molecular mechanism of exogenous MT for post-harvest preservation were evaluated in wax apple fruit. Results showed that MT treatment remarkably reduced decay incidence and the accumulation of excess reactive oxygen species (ROS), but increased the activity of antioxidant enzymes, suggesting that exogenous MT alleviates the post-harvest decay of wax apple by regulating the balance between ROS production and antioxidant system. Meanwhile, the gene expression was analyzed by transcriptome confirmed by quantitative PCR. This study provides insights into the regulatory mechanism and proper application strategies for post-harvest preservation of wax apple and other fruit though melatonin manipulation.